THE EFFECT OF BALI WASTE MANAGEMENT POLICIES ON WASTE TO ENERGY (WTE) INPUT CHARACTERISTICS IN SARBAGITA BASED ON SYSTEM DYNAMIC APPROACH - Matudilifa Yusuf, Deviana
In addition to being a concentrated place of population in the province of Bali, Sarbagita, which consists of Denpasar, Badung, Gianyar, and Tabanan has been designated as the center of tourism-based national economic activity. Population growth and tourism development in Sarbagita can lead to a faster increase in waste generation. To support population and tourism activities, waste management system in Sarbagita needs to be improved through appropriate and sustainable waste management efforts. Various policies have been initiated, including single-use plastic ban policy, source-based waste management policy, Policy and Strategic Actions for Waste Management (Jakstrada) in the province of Bali, and Waste to Energy (WtE) development plan. Although it has its own role, each waste management effort is related to one another. This study was conducted to analyze the interaction of various waste management efforts in Sarbagita. The effect of existing waste management system, single-use plastic ban policy, source-based waste management policy, and the Bali Provincial Jakstrada were studied on WtE input characteristics. The interaction between waste management efforts is depicted using system dynamic approach with STELLA program. The simulation is carried out on the model from 2020-2045 with 4 alternative policy scenarios. The policy scenarios analyzed are business as usual condition (scenario A), enhancement on single-use plastic ban policy (scenario B), enhancement on source-based waste management policy (scenario C), and enhancement on single-use plastic ban and source-based waste management policy towards achieving Jakstrada's waste reduction target (scenario D). The simulation results show that all scenarios are able to meet the minimum Lower Heating Value (LHV) requirement (6 MJ/kg) and input requirement (1,000 tons/day) for WtE operation. The recommended alternative is scenario D because it supports the achievement of Jakstrada's waste reduction target, opens up opportunity for future WtE development plan, extends WtE's operating period, and reduces the amount of waste that goes to Sarbagita landfill.